Kegiatan Seni sebagai Aktivitas Corporate Social Responsibility PT Kereta Api Indonesia - Yuliani Yuliani; Ferayanti Ginting (Gondang: Jurnal Seni dan Budaya, 2020)
The implementation of Corporate Social Responsibility activities done by state-owned companies is to enhance the positive image of a company.  It underlies the implementation of Corporate Social Responsibility activities conducted by PT KAI (Persero) in managing and developing the company's activities. Marching Band Locomotive is one of the activities managed by corporate social responsibility division, which consist of the employees of PT KAI and the society. The authors examine the Marching Band Locomotive activities from PT KAI as the research object because it is one of the marching band groups with lots of high achievement in arts however is still not too well known by public. The purpose of this research is to analyze the strategy done by PT KAI in managing Marching Band Locomotive activities. The conclusion of this research is that Marching Band Locomotive activity as a part of community relation program from PT KAI commits not only to build relationship with society, but also to give positive impact for the people who join Marching Band Locomotive from PT KAI. The implementation of Marching Band Locomotive activities by Corporate Social Responsibility division from PT KAI is also related to event promotion and it is communicated by Public Relations division through several media.